Well-structured 3D channels within GO-based membranes enable ultrafast wastewater treatment - Fu, Huaqiang; Wang, Zhe; Li, Peng; Qian, Wei; Zhang, Zixin; Zhao, Xin; Feng, Hao; Yang, Zhugen; Kou, Zongkui; He, Daping (Springer, 2022)
Graphene oxide (GO)-based membranes have been widely studied for realizing efficient wastewater treatment, due to their easily functionalizeable surfaces and tunable interlayer structures. However, the irregular structure of water channels within GO-based membrane has largely confined water permeance and prevented the simultaneously improvement of purification performance. Herein, we purposely construct the well-structured three-dimensional (3D) water channels featuring regular and negatively-charged properties in the GO/SiO2 composite membrane via in situ close-packing assembly of SiO2 nanoparticles onto GO nanosheets. Such regular 3D channels can improve the water permeance to a record-high value of 33,431.5 ± 559.9 L·m−2·h−1 (LMH) bar−1, which is several-fold higher than those of current state-of-the-art GO-based membranes. We further demonstrate that benefiting from negative charges on both GO and SiO2, these negatively-charged 3D channels enable the charge selectivity well toward dye in wastewater where the rejection for positive-charged and negative-charged dye molecules is 99.6% vs. 7.2%, respectively. The 3D channels can also accelerate oil/water (O/W) separation process, in which the O/W permeance and oil rejection can reach 19,589.2 ± 1,189.7 LMH bar−1 and 98.2%, respectively. The present work unveils the positive role of well-structured 3D channels on synchronizing the remarkable improvement of both water permeance and purification performance for highly efficient wastewater treatment.
Keywords: graphene oxide; membranes; wastewater treatment; water channels; charge-selectivity